LOSS OF RIGHT CHOICE: Ethical Quandary in the Wake of Coronavirus - Ferrao, Victor (Journal of Dharma, 2020)
The coronavirus pandemic along with large scale destruction of human life has triggered a collapse of our moral principles and ethical values. We are facing an inescapable ethical responsibility as we seem to have a new power to cough another person to death. This study attempts to seek an equate response to our moral quandaries. The study attempts to consider the moral culpability of akratic actions under the precarious conditions of inescapable vulnerabilities introduced by coronavirus. This consideration of weakening of human will or agency is profoundly significant to account for the morality of human actions, triggered through customised advertisements or messages to targeted individuals as a result Big Data analytics to serve the interest of commerce or politics.